2009
DOI: 10.1159/000273266
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Proliferation and Hepatic Differentiation of Human Adipose-Derived Stem Cells

Abstract: Human adipose-derived stem cells possess a lot of stem cell characteristics, so they may be considered a source of stem cell population. On the basis of that, we have investigated the hepatic potential of adipose-derived stem cells, obtained from liposuction, following two differentiation protocols. In the first procedure, medium was supplemented with epidermal growth factor (EGF), basic fibroblast growth factor, hepatocyte growth factor (HGF) and nicotinamide; the second involved the addition of factors such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 91 publications
1
25
0
6
Order By: Relevance
“…Following studies proved that DFAT cells can also be derived from the subcutaneous white adipose tissue (WAT) from various species, including human [17], rats [16], mouse [18] and cattle [8]. Because of the wide application of free-fat transfer and plastic liposuction [21][22], large amount of human DFAT cells can be derived by those convenient ways for autologous tissue engineering and reconstruction purposes. The dispersion and digestion process of WAT resembles the routine method of ASCs culture.…”
Section: Establishment Of Dfat Cellsmentioning
confidence: 99%
“…Following studies proved that DFAT cells can also be derived from the subcutaneous white adipose tissue (WAT) from various species, including human [17], rats [16], mouse [18] and cattle [8]. Because of the wide application of free-fat transfer and plastic liposuction [21][22], large amount of human DFAT cells can be derived by those convenient ways for autologous tissue engineering and reconstruction purposes. The dispersion and digestion process of WAT resembles the routine method of ASCs culture.…”
Section: Establishment Of Dfat Cellsmentioning
confidence: 99%
“…Embryonic stem cells may virtually differentiate into any tissue or organ, but due to ethical and technical issues associated with their use, attention has focused on mesenchymal stem cells. Mesenchymal stem cells are adult stromal multipotent progenitor cells having the capacity to differentiate into cells of mesenchymal lineage, including bone, fat, and cartilage~Meirelles & Nardi, 2009!, and displaying plasticity beyond their conventional mesodermal lineage~Widera et al, 2007;Coradeghini et al, 2010;Jang et al, 2010;Al Battah et al, 2011;Estrela et al, 2011!. Multipotent mesenchymal stromal cells~MSCs! exist in many different human organs, such as bone marrow~Cam-pagnoli et al, 2001!, placenta~In't Anker et al, 2004!, skeletal muscle~Williams et al, 1999!, fat~Zuk et al, 2001, 2002Torio-Padron et al, 2010!, andumbilical cord blood Bieback et al, 2004!. Oral cavity was also proved to be a valuable source of MSCs that can be isolated from accessible tissue resources and expanded in vitro, providing an important reservoir of stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Fat is an active and dynamic tissue composed of several different cell types, including adipocytes, fibroblasts, smooth muscle cells, endothelial cells, and adipogenic progenitor cells called pre-adipocytes [30], [31], [32]. Stem cells isolated from lipoaspirates have demonstrated a broad in vitro adipogenic, chondrogenic, osteogenic, and myogenic lineage commitment [33], [34] as well as differentiation into pancreatic cells, hepatocytes, and neurogenic cells [35], [36], [37]. Cytometric analysis of adipose-derived stem cells (ASCs) has shown that these cells do not express CD31 and CD45, but do express CD34, CD73, CD105, and the mesenchymal stem cell marker CD90 [38], [39].…”
Section: Efficacy Of Lipofillingmentioning
confidence: 99%